2019
DOI: 10.1093/mnras/stz227
|View full text |Cite
|
Sign up to set email alerts
|

The Milky Way like galaxy NGC 6384 and its nuclear star cluster at high NIR spatial resolution using LBT/ARGOS commissioning data

Abstract: We analyse high spatial resolution near infra-red (NIR) imaging of NGC 6384, a Milky Way like galaxy, using ARGOS commissioning data at the Large Binocular Telescope (LBT). ARGOS provides a stable PSF FWHM = 0. 2−0. 3 AO correction of the ground layer across the LUCI 2 NIR camera 4 ×4 field by using six laser guide stars (three per telescope) and a natural guide star for tip-tilt sensing and guiding. Enabled by this high spatial resolution we analyse the structure of the nuclear star cluster (NSC) and the cent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 97 publications
(134 reference statements)
0
10
0
Order By: Relevance
“…25 We exploit this data to look for the possible presence of multiple lensed images of the quasar generated by the presence of the z=0.711 elliptical galaxy located 1 6 NNE from the quasar (see Section 5.7). First, we construct a spatially variable PSF model and evaluate it at the quasar location; for further details, see Farina et al (2018) and Georgiev et al (2019). Next, we use this model to subtract both the emission from both the quasar and the close-by galaxy using the GALFIT v3.0.5 package (Peng et al 2010(Peng et al , 2011; see also our Figure 16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 We exploit this data to look for the possible presence of multiple lensed images of the quasar generated by the presence of the z=0.711 elliptical galaxy located 1 6 NNE from the quasar (see Section 5.7). First, we construct a spatially variable PSF model and evaluate it at the quasar location; for further details, see Farina et al (2018) and Georgiev et al (2019). Next, we use this model to subtract both the emission from both the quasar and the close-by galaxy using the GALFIT v3.0.5 package (Peng et al 2010(Peng et al , 2011; see also our Figure 16).…”
Section: Discussionmentioning
confidence: 99%
“…The total time on targets was 660 s, divided in 263 individual 2.51 s exposures. The data reduction has been performed with standard IRAF routines following the procedure described in Farina et al (2018) and Georgiev et al (2019). We registered Figure 15.…”
Section: Appendix a Atlas Of The Quasars Part Of The Requiem Surveymentioning
confidence: 99%
“…The two most invoked scenarios to form NSCs are the infall of a star cluster towards the galaxy center, due to dynamical friction, and the inflow of gas to the nuclear region, triggering star formation in situ. Recent works by Kacharov et al (2018) and Georgiev et al (2019) have shown that different scenarios could have played a major role in different galaxies, but also that both of them could have provided different contributions to the same NSC. Lyubenova et al (submitted) supported cluster merging in a study including also FCC 177 and FCC 170.…”
Section: Nscs In the Fornax Clustermentioning
confidence: 99%
“…The data reduction process for producing the science image follows the steps described by Georgiev et al (2019) in their ARGOS commissioning paper. After a basic reduction, correcting for nonlinearity and persistence effects, bad pixel masking, and flat-fielding, sky frames were created from exposures spaced about 10 min apart in order to negate effects by the rapidly varying near-infrared atmosphere.…”
Section: Image Processingmentioning
confidence: 99%